Acute stress‐induced neuronal plasticity in the corticoid complex of 15‐day‐old chick, Gallus domesticus. Issue 4 (22nd June 2021) - Kumar, Adarsh; Arya, Hemlata; Tamta, Kavita; Maurya, Ram Chandra
Abstract: Several studies conducted on chicken have shown that a single stress exposure may impair or improve memory as well as learning processes. However, to date, stress effects on neuronal morphology are poorly investigated wherefore it was of interest to evaluate this further in chicks. Thus, the present study aims to investigate the role of single acute stress (AS) of 24 h food and water deprivation in neuronal plasticity in terms of spine density of the corticoid complex (CC) in 15‐day‐old chick, Gallus domesticus, by using three neurohistological techniques: Cresyl Violet, Golgi Colonnier, and Golgi Cox technique. The dorsolateral surface of the cerebral hemisphere is occupied by CC which can be differentiated into two subfields: an intermediate corticoid (CI) subfield (arranged in layers) and a dorsolateral corticoid (CDL) subfield. Based on different criteria such as soma shape, dendritic branching pattern, and dendritic spine density, two main moderately spinous groups of neuronal cells were observed in the CC, namely, projection neurons (comprising of multipolar and pyramidal neurons) and stellate neurons. In the present study, the stellate neurons have shown a significant decrease as well as an increase in their spine density in both CI and CDL subfields, whereas the multipolar neurons had shown a significant increase in their spine density in the CDL region only. The present study shows that AS induces neuronal plasticity in terms of spine density in both CI and CDL neurons. The morphological changes in the form of decreased dendritic branches due to stress have been observed in the CI region in comparison to CDL region, which could be linked to more effect of stress in this region. The avian CDL corresponds to the entorhinal cortex of mammals on the basis of neuronal morphology and bidirectional connections between adjacent areas. The projection neurons increase their branches and also their spine number to cope with the stress effects, while the stellate neurons show contrasting effect in their spine density. Therefore, this study will establish that slight modifications in natural stimuli or environmental changes faced by the animal may affect their dorsolateral forebrain which shows neuronal plasticity that help in the development of an adaptive capacity of the animal to survive under changing environmental conditions. Abstract : In present study, we have investigated the role of single acute stress (AS) in inducing the neuronal plasticity in the corticoid complex (CC) of 15 day's old chick, Gallus domesticus by using Cresyl Violet, Golgi Colonnier and Golgi Cox methods. Our study revealed the CC is present at the dorsolateral surface towards caudal end of the cerebrum and contains highly spinous multipolar, pyramidal and stellate neurons. All the neurons show remarkable fluctuations in their morphological features most especially in spine density and dendritic branching pattern as a result of AS effects that could have important outcomes for functions of the CC in emotion, cognition and memory.